Towards Auspicious Agricultural Informatization—Implication of Farmers’ Behavioral Intention Apropos of Mobile Phone Use in Agriculture - Mwalupaso, Gershom Endelani; Wang, Shangao; Xu, Zhangxing; Tian, Xu (Sustainability, 2019)
The success of agricultural development programs in Sub-Saharan Africa (SSA) is subject to the extent and nature of information communication technology (ICT) usage, particularly mobile phones. In comparison to other ICTs, the mobile phone is less demanding in terms of user capabilities, infrastructure requirements, and affordability. Mobile phone technology plays a vital role in facilitating the realization of benefits for farmers through access to useful agricultural information. However, up till now farmers' behavioral intention towards mobile phone use has hardly been evaluated yet it is a critical issue that policymakers and development partners need to comprehend. Is mobile phone use in agriculture dependent upon farmers’ behavioral intention? We address this topic using cross-sectional data from Zambia obtained through a two-stage sampling procedure. Our results establish that a strong association consistent with the theory of planned behavior (TPB) exists. This suggests that positive behavioral intention has a substantial likelihood to elicit auspicious agricultural informatization and consequently, household economic development. We further find that mobile phone ownership, family size, wealth, and marital status can significantly influence smallholders’ behavioral change towards mobile phone use in agriculture. Therefore, in an effort to promote sustainable agricultural information access in rural settings, our study strongly demonstrates the relevance of farmers’ behavioral intent towards mobile phone use, and also enriches the discussion on the implementation of mobile phone use for collecting agricultural information.